PENINGKATAN KEMAMPUAN MENULIS PERMULAAN MELALUI METODE DRILL DI TAMAN KANAK-KANAK AZ-ZIKRA BONE - Mulyaningsih, Eka; Akbar, Andi Khemal (Institut Agama Islam Negeri Bone, 2022)
This research aims to determine the improvement of basic writing skill through drill method in Az-Zikra Bone. It applied Classroom Action Research (CAR) which seek to examine and analyze in depth the basic writing skill of the children through drill method by using qualitative approach. The focus of the research is improving the basic writing skill through drill method at Az-Zikra Bone Kindergarten. The research subject were 15 children of Group A and 1 teacher. The data was collected through observation and documentation, then analyzed through descriptive qualitative analysis. The research was carried out into two cycles, and each cycle was carried out through planning, implementing, observation, and reflecting techniques. The result showed that using drill method improve the basic writing skill of the children in group A at Az-zikra Bone Kindergarten with two indicators; 1) imitating making vertical, flat, slanted, curved, and circular lines; 2) Bold letters